The Relationship between Stakeholder Marketing and Reciprocity in Eastern Europe: A Conceptual Analysis - Ron Berger; Moti Zviling (International School for Social and Business Studies, 2013)
This conceptual paper deals with important implications of 'reciprocity' in marketing in emerging and developing business environments, such as Eastern Europe. In mature, developed, high income, business systems, both transaction and relationship based marketing have been well researched. We posit that in less mature business systems, especially transition or emerging economies, there is a third way to look at marketing and exchange, which we call 'reciprocity-stakeholder marketing.' We believe that our framework shows the importance of reciprocity, a fundamental concept in business, for marketing in emerging environments such as Eastern Europe. This paper provides a meaningful starting point for empirical research for developing strategies in Eastern Europe.